Pain management in the traumatized chest - Gnazzo, Jorge (Cirugía del Uruguay, 1990)
Pain relief in any patient is pointless disagreement and the way to achieve it may be as variable as the arsenal of painkillers with which we count in the middle. Purpose in the traumatized chest pain relief without causing depression respiratory system and, even more, is to achieve better ventilation by having a patient collaborate with the Respiratory physiotherapy.